Motivational attributions and demographic factors associated with U.S. dairy consumer attitudes toward a hypothetical animal welfare initiative - Robbins, Jesse; Proudfoot, Kathryn; Hemsworth, Lauren; Coleman, Grahame; Hemsworth, Paul; Van Os, Jennifer (Frontiers in Animal Science, 2026)
IntroductionThe dairy industry has responded to growing public concerns about animal welfare by developing various corporate social responsibility (CSR) initiatives aimed at demonstrating their commitment to animal welfare (AW). Unfortunately, little is known about how dairy consumers perceive these efforts. We conducted two studies of U.S. dairy consumers (n=344 and n=484) to assess their attitudes toward a fictitious AW-CSR initiative. Our objectives were to assess how attitudes toward the AW-CSR initiative and toward the company were affected by participants’ demographic factors and their perceived motivational attributions (i.e., strategic vs. altruistic) of the company for undertaking the AW-CSR initiative.MethodsIn both studies, adult participants were recruited online and were eligible if they consumed dairy products ≥ once/wk. Participants read a fictitious news article about an AW-CSR initiative focused on training dairy farm workers to appropriately handle cows. They then provided Likert-scale ratings of motivational attributions (whether they thought the initiative was strategic or altruistic) and their attitudes toward the initiative and the company. Spearman rank correlations followed by hierarchical multiple regressions were used to assess how attitudes toward the AW-CSR initiative and the company were associated with demographic factors and motivational attributions.Results and discussionAcross both studies, attitudes toward the AW-CSR initiative and the company were, on average, positive. Female gender was consistently associated with more positive attitudes toward the AW-CSR initiative. Higher age was associated with more positive attitudes in Study 2, but income, education, and political ideology were not associated with attitudes in either study. Rather than demographics, attitudes toward the AW-CSR initiative appeared to be largely associated with motivational attributions, with altruistic motivational attributions being a stronger predictor of positive attitudes compared to strategic motivational attributions. Future research could seek to better elucidate the process by which these motivational attributions are formed, which would help inform how dairy industry CSR initiatives could improve both animal welfare and consumer perceptions.